THE APPLICATION OF THE 't' TEST AND MARKOV CHAIN ANALYSIS IN BIOSTRATIGRAPHY OF 'X' WELL - Panuju Panuju; Mufdi Firdaus (Testing Center for Oil and Gas LEMIGAS, 2004)
There is no habit in biostratigraphers to apply the statistic methods to solve problems in their jobs, whereas in fact these methods are very useful when conventional ways failed. The use of this method has become very important in reservoir scale where microfossil content is low and indicator species is rare or absent. Applying biozonation in reservoir scale is much less reliable since reservoir layers are mostly below zonal resolution, so that the application of high resolution biostratigraphy is needed. In this case, the integration of biometric study and 't' or 'f' test can be used to define bioevent precisely. In sequence stratigraphy, data of depositional environment in various system tracts that determined using microfossil assemblage are very important. However, for the reasons of barren or no samples, this information might not be obtained by biostratigraphy or other methods. Due to the geological cycle and repeatable nature of depositional sequence, Markov Chain analysis can be used to predict the lost information about environment of deposition.